Memahami Konsep Dua Kodrat Yesus: Sebuah Tinjauan Teologis Menurut Injil Yohanes 1 - Lawolo, Aprianus (Sekolah Tinggi Agama Kristen Diaspora Wamena, 2022)
This study tries to answer the theological concept of the two unmixed natures of Jesus based on the Gospel of John 1. Where the two natures in the person of Jesus become one of the most important doctrines in Christianity. Through His incarnation of the virgin Mary, Jesus Christ obtained His humanity through His eternally possessed divinity. However, there have been various accounts of the second, such as the nature of Jesus. Arianism believes that the divinity of Jesus was imperfect. Apart from Arianism, adoptionism is an understanding that believes that Jesus was only a creation of God who was